Gas proportional scintillation counters with a CsI-covered microstrip plate UV photosensor for high-resolution X-ray spectrometry - Veloso, J. F. C. A. (2001)
A xenon-filled gas proportional scintillation counter for X-ray spectrometry is described. The detector uses a microstrip plate covered with a thin CsI film as a photosensor rather than the usual photomultiplier tube. The achieved energy resolution for 5.9 keV X-rays is 12% when the microstrip is operated within the xenon volume and 10.5% when the microstrip is operated in a P-10 environment, separated from the xenon volume by a quartz window.